Kinerja Pejabat Pembuat Akta Tanah Sementara Dalam Pengelolaan Bea Perolehan (BPHTB) di Kabupaten Indramayu - Bastaman, Komir (ijd-demos, 2019)
This study examines and analyzes the Performance of Temporary Land Deed Makers (PPATS) in the Management of Land or Building Acquisition Fees (BPHTB) in Sukra District, Indramayu Regency. The research approach used is a qualitative approach that is a research procedure that describes the facts and explains the object of research as well as digging the information needed in accordance with reality as it is. The results of the study illustrate that first The quality of PPATS officials especially in Sukra District in managing BPHTB is still not optimal, it can be seen from the realization that has not reached the target set by the Regional Government in accordance with the existing potential, even for the 2015 target it fell from the realization to previous year; second Quantity of results of work carried out by PPATS Officers in managing BPHTB in the Sukra District area is still not effective because the results achieved are not in accordance with the targets set by the regional government in terms of the potential that exists in the Sukra District area; third The use of time carried out by PPATS Officers in Sukra District in accordance with working hours ie from Monday to Friday Collection of BPHTB is carried out after there is a sale and purchase transaction of land and / or building and a deed of sale and purchase (AJB) conducted by PPATS Officials; fourt Cooperation of PPATS Officials in Sukra District with the community is already good, it's just that there are still many people who are not aware of the benefits of Tax, that is because the level of public education in Sukra District is still low on average plus the level of taxpayer knowledge that is still lacking. Penelitian ini mengkaji dan menganalisis mengenai Kinerja Pejabat Pembuat Akta Tanah Sementara (PPATS) dalam Pengelolaan Bea Perolehan Atas Tanah Atau Bangunan (BPHTB) di Kecamatan Sukra Kabupaten Indramayu. Pendekatan penelitian yang digunakan adalah pendekatan kualitatif yaitu prosedur penelitian yang menggambarkan fakta-fakta dan menjelaskan objek penelitian serta menggali informasi yang dibuthkan sesuai dengan kenyataan sebagaimana adanya. Hasil penelitian memberikan gambaran bahwa pertama Kualitas Pejabat PPATS khususnya di Kecamatan Sukra dalam pengelolaan BPHTB masih kurang maksimal, itu terlihat dari realisasi yang belum mencapai target yang sudah ditentukan oleh Pemerintah Daerah sesuai dengan potensi yang ada, bahkan untuk target tahun 2015 turun dari realisasi untuk tahun sebelumnya; kedua Kuantitas hasil pekerjaan yang dilaksanakan oleh Pejabat PPATS dalam mengelola BPHTB di wilayah Kecamatan Sukra masih belum efektif karena hasil yang dicapai tersebut belum sesuai target yang telah ditetapkan oleh pemerintah daerah dilihat dari potensi yang ada di wilayah Kecamatan Sukra; ketiga Penggunaan waktu yang dilaksanakan oleh Pejabat PPATS di Kecamatan Sukra sesuai dengan jam kerja yaitu dari hari Senin sampai dengan Jum’at. Pemungutan BPHTB dilaksanakan setelah ada transaksi jual beli tanah dan/atau bangunan dan melakukan akta jual beli (AJB) yang dilakukan oleh Pejabat PPATS; ke-empat Kerjasama Pejabat PPATS di Kecamatan Sukra dengan masyarakat sudah baik, hanya saja masih banyak masyarakat belum menyadari manfaat Pajak, itu dikarenakan tingkat pendidikan masyarakat di Kecamatan Sukra rata-rata masih rendah ditambah lagi tingkat pengetahuan wajib pajak yang masih kurang.